Pengembangan Jobsheet Berbasis Project Based Learning pada Training Kit Pembangkit Listrik Tenaga Surya untuk Meningkatkan Kreativitas dan Inovatif Peserta Didik - Hafid Andika Faturachman; Joko Joko (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
This study aims to develop a feasible Project Based Learning (PjBL)-based jobsheet on a Solar Power Plant (PLTS) training kit to solve the lack of learning media usage in the Electrical Power Installation subject for class XI TITL at SMK Semen Gresik. This research uses the Research & Development (R&D) method with the ADDIE model (Analyze, Design, Development, Implementation, Evaluation). The subjects of this study were 22 students of class XI TITL. The validity test results obtained an average score of 87% from material experts and 88% from media experts, both categorized as "highly valid". The practicality test from student responses obtained a score of 83%, categorized as "highly practical". Furthermore, the effectiveness test using the N-Gain score obtained a value of 0.646, which falls into the "medium" category. The Paired Sample T-Test showed a significance value of 0.000, indicating a significant difference between pretest and posttest scores. It can be concluded that the developed PjBL-based jobsheet is highly feasible, practical, and effective in increasing students' creativity and innovativeness.